Determination of potential inhibitors based on isatin derivatives against SARS-CoV-2 main protease (mpro): a molecular docking, molecular dynamics and structure-activity relationship studies. Issue 7 (3rd May 2022) - Badavath, Vishnu Nayak; Kumar, Akhil; Samanta, Pralok K.; Maji, Siddhartha; Das, Anik; Blum, Galia; Jha, Anjali; Sen, Anik
Abstract: SARS-COV-2, the novel coronavirus and root of global pandemic COVID-19 caused a severe health threat throughout the world. Lack of specific treatments raised an effort to find potential inhibitors for the viral proteins. The recently invented crystal structure of SARS-CoV-2 main protease (M pro ) and its key role in viral replication; non-resemblance to any human protease makes it a perfect target for inhibitor research. This article reports a computer-aided drug design (CADD) approach for the screening of 118 compounds with 16 distinct heterocyclic moieties in comparison with 5 natural products and 7 repurposed drugs. Molecular docking analysis against M pro protein were performed finding isatin linked with a oxidiazoles (A2 and A4 ) derivatives to have the best docking scores of −11.22 kcal/mol and −11.15 kcal/mol respectively. Structure-activity relationship studies showed a good comparison with a known active M pro inhibitor and repurposed drug ebselen with an IC50 value of −0.67 μM. Molecular Dynamics (MD) simulations for 50 ns were performed for A2 and A4 supporting the stability of the two compounds within the binding pocket, largely at the S1, S2 and S4 domains with high binding energy suggesting their suitability as potential inhibitors of M pro for SARS-CoV-2. Abstract : UF0001 Abstract : Communicated by Ramaswamy H. Sarma